Selective Extraction and Efficient Binding in a Protic Solvent of Contact Ion Triplets by Using a Thiourea‐Based Bis‐Calix[6]arene Receptor. Issue 24 (5th July 2013) - Moerkerke, Steven; Le Gac, Stéphane; Topić, Filip; Rissanen, Kari; Jabin, Ivan
Abstract: We report a D 3 h ‐symmetric tail‐to‐tail bis‐calix[6]thiourea5 that displays two divergent cavities triply connected by thiourea linkages. This calix[6]tube was efficiently synthesized through a [1+1] macrocyclization reaction and characterized by X‐ray diffraction analysis. The binding properties of this heterotritopic receptor were evaluated in a protic environment (i.e., CD3 OD/CDCl3 ) through NMR studies. Thus, bis‐calix[6]thiourea5 exhibits a remarkable ability in the cooperative complexation of an anion sandwiched between two ammonium ions, a high selectivity for ammonium sulfate salts being observed. The anion is bound through multiple hydrogen‐bonding interactions at the thiourea binding site and is in contact with the two ammonium ions accommodated in the cavities. The resulting quaternary complexes are rare examples of cascade complexes involving organic cations. Moreover, when wrapping around the anion, the thiourea linkers adopt a helical shape and the resulting chirality is sensed by the bound cations. In comparison with the parent amido‐ or urea‐based bis‐calix[6]arenes1 and2, bis‐calix[6]thiourea5 behaves as a much more efficient receptor for organic ion triplets. This strengthening of the binding properties is likely due to the higher acidity of the thiourea groups and to their poor ability to self‐associate. Interestingly, we have obtained the first X‐ray structure of a bis‐calix[6]arene‐based cascade complex. It shows that these host–guest complexes are stabilized through a dense network of hydrogen‐bonding interactions. Finally, although sulfate salts are better recognized in CD3 OD/CDCl3, the selective extraction of ammonium nitrate salts from water to chloroform was evidenced through NMR studies. This remarkable result can be rationalized by the weaker hydration of the nitrate anion and its good geometrical complementarity with the tris‐thiourea binding site. Abstract : A tubular D 3 h ‐symmetric bis‐calix[6]arene displaying three convergent thiourea groups has been efficiently synthesized. In comparison with the parent amido‐ and urea‐based receptors, this new calix[6]tube exhibits strong and unique binding properties towards contact ion triplets in a protic environment. In particular, the selective extraction of ammonium nitrates from water has been evidenced.